ANALYSIS OF THE EFFECTIVENESS OF APPROACHES TO DETERMINING THE CAPITAL REQUIREMENTS FOR COVERING INVESTMENT RISKS IN PORTFOLIOS WITH INCLUSION OF ALTERNATIVE INVESTMENTS AND CRYPTOCURRENCIES - KAMINSKYI, Andriy; BUTYLO, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article delves into evaluating the capital requirements of institutional investors for managing the risks in portfolios encompassing alternative investments and cryptocurrencies. It scrutinizes the progression of risk management approaches, particularly the unique challenges posed by alternative assets and digital currencies. In this study, Conditional Value at Risk (CVaR) is established as a principal indicator for assessing capital requirements for investment risk coverage. Portfolios are formulated based on principles of risk minimization, return optimization per unit of risk, and categories of traditional assets, alternative assets, cryptocurrencies, and their various combinations. This varied approach permits an extensive exploration across different investment scenarios and strategies. Following portfolio formations, we delve into the examination of diverse econometric and mathematical tools, including the Historical Method, Parametric Method, Cornish-Fisher Method, Monte Carlo Method, GARCH (Generalized Autoregressive Conditional Heteroskedasticity), EWMA (Exponentially Weighted Moving Average), and paired copula constructions method. Each method is scrutinized for its efficacy and precision in determining risks within these diverse portfolios. The study culminates by identifying the most efficient methodologies under varying market conditions. The focus is placed on the advantages of the copula approach in estimating investors’ needs for capital to cover risk. This insight is crucial for investors and portfolio managers to tailor their risk management strategies, aligning with the evolving and dynamic nature of the investment markets. It underscores the significance of a multifaceted approach in understanding and minimizing investment risks, contributing to more informed and strategic decision-making in investment risk management.